Of parliament and presentism: electoral representation and future generations in Germany. Issue 1 (2nd January 2023) - Kinski, Lucy; Whiteside, Kerry
ABSTRACT: Always pressured by electoral deadlines, parliaments are often seen as a weak link in the sustainability politics of representative democracies. Scholars reviewing possible democratic reforms for overcoming parliamentary presentism often reference Germany's Parliamentary Advisory Council for Sustainable Development (PBnE). What does this Council's record reveal about the practicality of representing future generations through parliamentary bodies? We combine a philosophical-historical interpretation of Germany's approach to future-generations issues with an empirical analysis of the PBnE's record. We conclude that while the PBnE has brought greater formal attention to sustainability in the parliamentary process, the idea of enhanced future-regarding representation remains problematic. Counterpoising different sustainability-oriented institutions grounded in diverse forms of democratic legitimacy is a more promising path.